A new holder/container with a porous cover for atomic layer deposition on particles, with transport analysis and detailed characterization of the resulting materials. (12th October 2020) - Shah, Dhruv; Patel, Dhananjay I.; Major, George H.; Argyle, Morris D.; Linford, Matthew R.
Abstract : Atomic layer deposition (ALD) is widely used in the semiconductor and materials industries for depositing thin films. Here, we describe a holder/container for performing ALD on particles that does not require agitation. This device contains a broad, shallow, circular recess that holds the particles. Two different frits and combinations of stacked meshes were explored as a cover to this holder to restrict the movement of the particles while still allowing good conductance of the ALD reagent gases. A mathematical discussion of the diffusion through the frits and stacked meshes is presented. As confirmed by spectroscopic ellipsometry (SE) on planar witness silicon shards, consistent, high‐quality film growth took place inside and outside the holder. The performance of the holder was demonstrated with ~5‐μm zirconia particles that were coated with alumina from trimethylaluminum (TMA) and water, and with zinc oxide from diethylzinc (DEZ) and water. Deposition on different amounts of particles was investigated (50, 100, 200, and 500 mg). Parasitic chemical vapor deposition (CVD) appeared to be present when a greater number of particles or meshes were used. ALD coating on particles was also confirmed by X‐ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), and energy‐dispersive X‐ray spectroscopy (EDS).